Proceso de atención de enfermería a paciente de 32 años con pancreatitis aguda - Arteaga Caice, Alexandra Nohely (2021)
Acute pancreatitis is attributed as the clinical syndrome that is characterized by the sudden presence of abdominal pain, with the advancement of serum pancreatic enzymes, a necrotizing-type inflammation occurs, the diagnosis is based on the clinic and support based on The laboratory results in which the presence of acute abdominal pain should be considered and the finding in the complementary tests as important data shows the levels of amylase or lipase are found. This clinical case study writes to a 32-year-old patient, who went to hospital unit after presenting symptomatic picture characterized by abdominal pain located in hypogastric region and with irradiation to left hypochondria and region lumbosacra of moderate intensity, astenic state, hyperthermia of 38.4 C, vomiting, nausea decreased appetite, prior to admission laboratory tests were performed with amylase levels and serum lipases, 3 times above normal value, proceeded with the protocol of the hospital and the application of the nursing care process with the application of essential tools such as the taxonomies Nanda, Nic, Noc that allowed to provide the proper nursing care and through medical treatment, administration of hydroelectrolytic supports, fasting and induction of analgesia the recovery of pancreatic function was achieved the procedure performed in the patient was retrograde cholangiopancreatography with endoscopy, once the previous measures were performed, the evaluation of these interventions resulting in the total improvement of the clinical status of the patient to study.